Mental condition and specificity of mental disorders in a group of workers from southern Poland: A research report - Bernadetta Izydorczyk (Nofer Institute of Occupational Medicine, 2018)
Background The aim of this work is to provide empirical evidence regarding types and increasing prevalence of mental disorders affecting Polish working population in the years 2014-2016. The research questions concerned the specific characteristics of the types of mental disorders and their prevalence as well as the differences between males and females. Material and Methods Types of mental disorders were investigated using a clinical method, a structured interview, as well as medical record data gathered in the years 2014-2016 in one mental health treatment center. The study was conducted in the population of 1578 working individuals aged 18-64 years old, in various forms of employment, including flexible employment (self-employment, task assignment agreement) and contract employment. The research population consisted of 998 females and 580 males, aged 18-64 years old. The study aimed at investigating types and the prevalence rate of mental disorders developed in the examined working Poles, also with reference to the sex of the study participants as well as the age at which they started seeking treatment. Results The prevailing disorders include neurotic disorders; diagnosed according to the 10th Revision of the International Statistical Classification of Diseases and Related Health Problems (ICD-10) classification as a range of anxiety disorders, mixed anxiety-depressive disorders, stress-related and somatoform disorders; as well as personality disorders. The prevalence rate of the aforementioned disorders was found to be higher among working females than in the group of working males. Conclusions The overall study conclusions based on the research data analysis point to the fact that the prevalence rate of various types of mental disorders displayed by the examined working males and females increased significantly in the years 2014-2016. Med Pr 2018;69(1):13-28